Progesterone vs placebo therapy for women with epilepsy: A randomized clinical trial - Herzog, A.G. (Lippincott Williams & Wilkins, 2012)
OBJECTIVE: To assess progesterone treatment of intractable seizures in women with partial epilepsy. METHODS: This randomized, double-blind, placebo-controlled, phase III, multicenter, clinical trial compared the efficacy and safety of adjunctive cyclic natural progesterone therapy vs placebo treatment of intractable seizures in 294 subjects randomized 2:1 to progesterone or placebo, stratified by catamenial and noncatamenial status. It compared treatments on proportions of ≥50% responders and changes in seizure frequency from 3 baseline to 3 treated menstrual cycles. RESULTS: There was no significant difference in proportions of responders between progesterone and placebo in the catamenial and noncatamenial strata. Prespecified secondary analysis showed that the level of perimenstrual seizure exacerbation (C1 level) was a significant predictor of responders for progesterone but not placebo. With increasing C1 levels, responders increased from 21% to 57% with progesterone vs 19% to 20% with placebo. Reductions in seizure frequency correlated with increasing C1 levels for progesterone but not placebo, progressing from 26% to 71% for progesterone vs 25% to 26% for placebo. A prespecified clinically important separation between progesterone and placebo responders (37.8% vs 11.1%; p = 0.037) was realized among 21.4% of women who had C1 level ≥3. CONCLUSION: There was no difference in the primary outcome of ≥50% responder rates between progesterone vs placebo for catamenial or noncatamenial groups. Post hoc findings suggest that the level of perimenstrual seizure exacerbation is a significant predictor of responder rate with progesterone and that progesterone may provide clinically important benefit for a subset of women with perimenstrually exacerbated seizures. CLASSIFICATION OF EVIDENCE: This study provides Class III evidence that cyclic progesterone is ineffective in women with intractable partial epilepsy. Post hoc analysis identified a subset of women with higher levels of perimenstrual seizure exacerbation that were responsive to treatment.